Food Communication Sentiment Analysis on Free Nutritious Meal Program's: From Negative Bias to Policy Legitimacy - Setyaningsih, Rila; Santoso, Didik Haryadi; Shovmayanti, Noor Afy (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The rapid development of digital technology, particularly Artificial Intelligence (AI), has significantly transformed communication practices, including the field of da’wah. This study aims to examine the integration of Islamic communication ethics in the utilization of AI for da’wah in the digital era. Employing a qualitative approach with a literature review method, this research analyzes various scholarly sources related to Islamic communication ethics, digital da’wah, and AI technology. The findings reveal that while AI offers substantial opportunities in expanding the reach, efficiency, and personalization of da’wah messages, it also presents ethical challenges such as the risk of misinformation, distortion of religious messages, loss of humanistic values, and weakened scholarly authority. In response, Islamic communication ethics grounded in principles such as qaulan sadidan (truthfulness), qaulan layyinan (gentleness), qaulan balighan (effectiveness), and tabayyun (verification) serve as essential guidelines to ensure that AI-based da’wah remains accurate, ethical, and aligned with Islamic values. The study concludes that the integration of ethical principles with technological innovation is crucial, where AI functions as a supportive tool rather than a replacement for human da’i. This integration not only enhances the effectiveness of da’wah but also preserves its moral and spiritual integrity in the digital age.